2022
DOI: 10.1002/fsn3.3056
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of kabuli and desi chickpea (Cicer arietinum L.) cultivars grown in Xinjiang, China

Abstract: Chickpeas are a very important legume crop and have abundant protein, carbohydrate, lipid, fiber, isoflavone, and mineral contents. The chemical compositions of the four chickpea species (Muying‐1, Keying‐1, Desi‐1, Desi‐2) from Xinjiang, China, were analyzed, and 46 different flavonoids in Muying‐1 were detected. The moisture content ranged from 7.64 ± 0.01 to 7.89 ± 0.02 g/100 g, the content of starch in the kabuli chickpeas was greater than that in the desi chickpeas, the total ash content ranged from 2.59 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Whereas Ipekesen et al [ 45 ] and Sahu et al [ 46 ] found no difference in protein content, only in selected amino acids, when comparing desi and kabuli varieties. Remarkably, Xiao et al [ 36 ] described a higher starch amount in kabuli than in desi , but, again, no difference in protein concentration.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Whereas Ipekesen et al [ 45 ] and Sahu et al [ 46 ] found no difference in protein content, only in selected amino acids, when comparing desi and kabuli varieties. Remarkably, Xiao et al [ 36 ] described a higher starch amount in kabuli than in desi , but, again, no difference in protein concentration.…”
Section: Resultsmentioning
confidence: 94%
“…The differences found in the effect of heat treatment on the textural characteristics of the different chickpea varieties used in this study can be attributed to their different structural, morphological, and compositional characteristics. The PD chickpeas are categorized as desi (small, wrinkled, and dark-colored) [ 35 , 36 ], whereas BL and CA are kabuli varieties (large, smooth-coated, and white to cream-colored). PD chickpeas, due to their smaller diameter, reached the temperature of the cooking medium more quickly than larger chickpeas, thus affecting their structure and textural attributes, such as adhesiveness (greater in PD).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…originated in western Asia and the Near East and has a long history of cultivation. It ranks third in the world as the most important food legume [ 1 ]. It contains many healthful constituents including carbohydrates, protein, fiber, fat, and a variety of active ingredients [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the country has developed the ability to export kabuli-type chickpeas in the recent past, it also imports a large quantity of desi chickpeas to meet domestic demand. Desi chickpeas have the potential to be a source of different nutrients, including high-quality proteins made up of significant amounts of vital fatty acids, amino acids, minerals, trace elements, and proteins, viz., albumins and globulins [ 7 , 8 ]. Furthermore, there is the additional requirement of increasing chickpea production to meet the projected domestic chickpea demand of 17.5 mt by 2050 [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%